Interaction between landscape space and interior space in the architecture of recent educational buildings in Latvia - Grietēna, Aija; Ziemeļniece, Aija (Landscape Architecture and Art, 2025)
This study examines the interaction between landscape space and interior architecture in contemporary Latvian school buildings, highlighting its importance in achieving sustainable spatial integration. It builds on a 2019 study and aligns with current European and global sustainability initiatives. Despite demographic decline, Latvia continues to invest in new school construction and renovation, some of which have received national architectural awards. The research identifies both achievements and shortcomings, especially in interdisciplinary collaboration and the integration of timber architecture, offering recommendations to advance sustainable public architecture in Latvia.